Haematological abnormalities and pharmacotherapy in severe acute respiratory syndrome corona virus 2 - Raghute, Latesh B.; Dudhgaonkar, Sujata; Uike, Pravin S.; Jaiswal, Kavita M. (International Journal of Basic & Clinical Pharmacology, 2021)
The first case of SARS-CoV-2 (severe acute respiratory syndrome corona virus 2) was reported in Wuhan, China at the end of year 2019. It shows flu-like symptoms, but anosmia, fatigue, persistent cough and loss of appetite, that collectively might spot individuals with COVID-19. The aim of writing this review was to gather the information about blood abnormalities and pharmacotherapy for COVID-19 as a resource for healthcare professionals. A blood workup as well as continuous tracking hematological changes could divulge the risks of disease progression. The indirect indicators such as C-reactive protein (CRP), D-dimer, albumin, ferritin and LDH levels which are used as markers to estimate the severity of COVID-19 infection and prognosis. The most common hematological findings include lymphocytopenia, neutrophilia, eosinopenia, mild thrombocytopenia and less frequently, thrombocytosis. Clinical management includes prophylactic and therapeutic measures. Supportive care including supplemental oxygen and mechanical ventilatory support as and when indicated. Several class of drugs like anti-malarial, anti-viral, anti-inflammatory drugs are being used for the treatment and prevention of COVID-19. The target for development of most of the vaccine for COVID-19 is S protein of the corona virus. Various vaccines available for use across the globe are COVAX, Covishield, Moderna, Johnson and Johnson, Sputnik V, Novavax, Sinopharm, SinoVac. Serial monitoring of hematological manifestations is recommended and the treating doctor should stay vigilant and consider proper screening. The therapeutic intention is to decrease viral load and pharmacological thrombo-prophylaxis in high risk patients.